2017
DOI: 10.1002/pbc.26836
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistency in classifying vascular anomalies: What's in a name?

Abstract: Background Vascular anomalies are a heterogeneous group of disorders seen in children and adults. A standard nomenclature for classification has been offered by the International Society for the Study of Vascular Anomalies (ISSVA). Its application is important for communication among the multiple specialties involved in the care of patients and for planning treatment, as well as for research and billing. We hypothesized that terminology still is not uniformly applied, and that this could have an impact on trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Both across specialties and within associated disciplines, it has been shown that there is inconsistency in the terminology used to describe vascular anomalies [39]. Obtaining an accurate diagnosis with appropriate terminology is important for properly managing patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both across specialties and within associated disciplines, it has been shown that there is inconsistency in the terminology used to describe vascular anomalies [39]. Obtaining an accurate diagnosis with appropriate terminology is important for properly managing patients.…”
Section: Discussionmentioning
confidence: 99%
“…RV, right ventricle; IVS, interventricular septum; LV, left ventricle. The ISSVA classification standards have been published; however, there is a lack of consensus regarding the understanding of whether vascular anomalies are tumors or malformations (16). Initially, they were classified according to factors such as vascular distortion and structure.…”
Section: Figure 2 | (Ab)mentioning
confidence: 99%
“…1 A pesar de que esta clasificación tiene más de 20 años de vigencia, y de los diversos intentos enfocados a divulgarla, hasta la fecha se siguen utilizando, erróneamente, los términos "hemangioma", "hemolinfangioma" o "linfangioma" para describir tumores vasculares y malformaciones, aludiendo solo al componente vascular, sin diferenciar entre el carácter proliferativo o malformativo propio de cada una; esto deriva en una atención inadecuada del paciente. 5 De aquí la importancia de que el médico de primer contacto, el pediatra y los especialistas de las…”
Section: Introductionunclassified